Effect of high speed drilling on residual stress on a hole of PCB material - 203898 Thong, Pheng Heng (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 2003